2003
DOI: 10.1200/jco.2003.02.061
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Temozolomide Plus Thalidomide for the Treatment of Metastatic Melanoma

Abstract: The combination of temozolomide plus thalidomide seems to be a promising and well-tolerated oral regimen for metastatic melanoma that merits further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
2
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(76 citation statements)
references
References 19 publications
2
69
2
3
Order By: Relevance
“…Temozolomide has been combined with thalidomide (Hwu et al, 2003) or with interferon-a, using schedules similar to that used here, or with daily or three-times daily administration for 6 weeks out of eight. Most promising results have been obtained in combination with thalidomide (Danson et al, 2003), but that combination requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Temozolomide has been combined with thalidomide (Hwu et al, 2003) or with interferon-a, using schedules similar to that used here, or with daily or three-times daily administration for 6 weeks out of eight. Most promising results have been obtained in combination with thalidomide (Danson et al, 2003), but that combination requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the response rate of melanoma to dacarbazine or TMZ is only ∼20%. Attempts to improve efficacy of TMZ through combination therapy with drugs such as cisplatin, docetaxel, thalidomide, IFN, and irinotecan have shown no clear benefits in response rates, median time to progression, or overall survival (7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…In a basic fibroblast growth factor (bFGF)-induced angiogenesis assay performed in rabbit cornea, it was shown that thalidomide significantly decreased the formation of new vessels 7 and inhibited vascular endothelial growth factor (VEGF)-induced angiogenesis. 8 Several clinical studies indicate that thalidomide may possess antineoplastic properties in myeloma, 9 melanoma, 10 hormonerefractory prostate carcinoma, 11 high-grade glioma, and Kaposi sarcoma. 12 Several considerations support the potential use of thalidomide in patients with HCC.…”
mentioning
confidence: 99%